Analysis of psychosocial risk factors through ISTAS 21 in a pharmaceutical industry (Horizontes de Enfermería, 2021)
Exposure to psychosocial risks has been increasingly frequent in recent years, causing consequences in the economy of companies and mental illnesses in workers. Work conditions incurrent circumstances of globalization increase the probability of exposure to risk factors at work. The objective of the research was to analyse the exposure of psychosocial risk factors in workers of a pharmaceutical company through the ISTAS 21 test. A quantitative, non-experimental, crosssectional, and descriptive study was carried out. The population under study was consisted of 50 workers from the Bagó pharmaceutical company. Through the survey, the ISTAS 21 test was applied, with 91 questions, calculating the psychosocial dimensions of psychological demands,active work and skills development, social support in the company, quality of leadership, compensation, and dual presence. According to the analysis of psychosocial risk factors through the test, the 5 groups of psychosocial dimensions measured by the questionnaire were observed, most of the workers obtained a high exposure with 90% dual presence; In compensations, insecurity with respect to the employment contract was manifested as high with 76%, the workers were concerned about job stability generating effects on mental health. It was concluded that the company should develop plans, psychosocial risk prevention programs as well as techniques for the proper management of work stress.
Keywords: Psychosocial risks; workers; occupational health; ISTAS 21; Dual Presence